Expression Profiles and Binding Properties of the Chemosensory Protein PxylCSP11 from the Diamondback Moth, Plutella xylostella (Lepidoptera: Plutellidae). Issue 5 (15th October 2020) - Fu, Shuhui; Li, Fangyuan; Yan, Xizhong; Hao, Chi
Abstract: The diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae) is one of the most destructive pests to cruciferous plants worldwide. The oligophagous moth primarily utilizes its host volatiles for foraging and oviposition. Chemosensory proteins (CSPs) are soluble carrier proteins with low molecular weight, which recognize and transport various semiochemicals in insect chemoreception. At present, there is limited information on the recognition of host volatiles by CSPs of P. xylostella . Here, we investigated expression patterns and binding characteristics of Pxyl CSP11 in P. xylostella . The open reading frame of Pxyl CSP11 was 369-bp encoding 122 amino acids. Pxyl CSP11 possessed four conserved cysteines, which was consistent with the typical characteristic of CSPs. PxylCSP11 was highly expressed in antennae, and the expression level of PxylCSP11 in male antennae was higher than that in female antennae. Fluorescence competitive binding assays showed that Pxyl CSP11 had strong binding abilities to several ligands, including volatiles of cruciferous plants, and (Z)-11-hexadecenyl acetate (Z11-16:Ac), a major sex pheromone of P. xylostella. Our results suggest that Pxyl CSP11 may play an important role in host recognition and spouse location in P. xylostella.